Severe hypoxia affects exercise performance independently of afferent feedback and peripheral fatigue - Millet, G. Y.; Muthalib, M.; Jubeau, M.; Laursen, P. B.; Nosaka, K. (Journal of Applied Physiology, 2012)
To test the hypothesis that hypoxia centrally affects performance independently of afferent feedback and peripheral fatigue, we conducted two experiments under complete vascular occlusion of the exercising muscle under different systemic O2 environmental conditions. In experiment 1, 12 subjects performed repeated submaximal isometric contractions of the elbow flexor to exhaustion (RCTE) with inspired O2 fraction fixed at 9% (severe hypoxia, SevHyp), 14% (moderate hypoxia, ModHyp), 21% (normoxia, Norm), or 30% (hyperoxia, Hyper). The number of contractions (performance), muscle (biceps brachii), and prefrontal near-infrared spectroscopy (NIRS) parameters and high-frequency paired-pulse (PS100) evoked responses to electrical muscle stimulation were monitored. In experiment 2, 10 subjects performed another RCTE in SevHyp and Norm conditions in which the number of contractions, biceps brachii electromyography responses to electrical nerve stimulation (M wave), and transcranial magnetic stimulation responses (motor-evoked potentials, MEP, and cortical silent period, CSP) were recorded. Performance during RCTE was significantly reduced by 10-15% in SevHyp (arterial O2 saturation, SpO2 = ~75%) compared with ModHyp (SpO2 = ~90%) or Norm/Hyper (SpO2 > 97%). Performance reduction in SevHyp occurred despite similar 1) metabolic (muscle NIRS parameters) and functional (changes in PS100 and M wave) muscle states and 2) MEP and CSP responses, suggesting comparable corticospinal excitability and spinal and cortical inhibition between SevHyp and Norm. It is concluded that, in SevHyp, performance and central drive can be altered independently of afferent feedback and peripheral fatigue. It is concluded that submaximal performance in SevHyp is partly reduced by a mechanism related directly to brain oxygenation.